EFL Teachers' Stress and Job Satisfaction: What Contribution Can Teacher Education Make? - Karim Sadeghi; Morteza Sa’adatpourvahid (Iranian Journal of Language Teaching Research, 2016)
The present study was conducted to find out the level of job satisfaction and stress among Iranian EFL teachers. More precisely, an attempt was made to investigate the main sources of EFL teachers’ stress, their level of satisfaction with the job and the relationship between occupational stress and instructors’ age, marital status and tenure. Using a localized self-reported questionnaire, adapted from Ferguson, Frost, and Hall (2012), data was collected from 149 EFL teachers working in Urmia, Iran. The analysis of the data revealed that 29.93% of the teachers reported feelings of stress in one way or another. In addition, more than one-third of the teachers claimed to be somewhat or very dissatisfied with their job. It was also observed that age, marital status and employment play significant roles in the level of occupational stress perceived by EFL teachers. Suggestions are offered for relieving teachers from stress and how teacher education programmes can contribute.